Analysis of Ear, Nose, Throat and Head & Neck Surgery Consultations and Diagnostic Accuracy in a Tertiary Care Hospital of Western Nepal - Rijal, Krishna Chandra; Koirala, Krishna Prasad; Ghimire, Bibek; Adhikari, Sangam (Journal of College of Medical Sciences-Nepal, 2023)
Introduction ENT cases are very common accounting for 25-40% of all hospital patient. Subspecialty consultations are a necessary part of comprehensive medical care that provide an opportunity for interactions between doctors and the exchange of knowledge and expertise that helps in quality patient management. Methods A descriptive cross-sectional study was conducted among patients asked for consultation in the Department of ENT and Head & Neck Surgery, Manipal Teaching Hospital from March 2022 to November 2022. Diagnosis made by ENT surgeon after relevant investigations was recorded. Analysis of diagnostic accuracy by non-ENT surgeons was carried out. Results Out of 8019 cases seen in the department of ENT and Head & Neck Surgery from 15th March 2022 to 25th November 2022, 400 cases were asked for consultations. Consultations were more frequently asked from Internal medicine and subspeciality followed by Emergency and Pediatrics department. The most common complaint in consultation sheet was throat pain. The commonest ENT and Head & Neck Surgery diagnosis was Allergic Rhinitis, followed by Presbyacusis and Acute Tonsillitis. Two hundred and twenty cases were asked for consultations with diagnosis from the primary department, out of which 183 had correct diagnosis. Conclusions Different departments do have difficulties in identifying and addressing ENT and Head & Neck Surgery cases and there is benefit from ENT and Head & Neck Surgery consultations. Furthermore, ENT and Head & Neck Surgery consultations do have high educational value for other departments and plays a vital role in patient management.